Mechanical engineering and social technology: structural design and building of a glass grinder for a recyclable materials collectors’ association - Passos, João Gabriel da Cruz; Alencar, Ana Flávia Oliveira; Barroso, Mariana dos Santos; Silva, Nathalia Caroline Spineli Forzan; do Nascimento, Valdecy Rodrigo; Muniz, Leandro Reis; de Sousa Malafaia, Artur Mariano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Recycling has an important role on the reduction of environmental impacts caused by production via raw materials. Due to its importance to the recycling process, this study aimed to help the Recyclable Material Collectors’ Association of the city of São João del-Rei, Minas Gerais, proposing a glass grinder design. The viability of the machine was evaluated, and the components were sized. After these steps, a structural design was made, using concepts related to Materials Selection, Mechanics of Materials, Mechanical Design, Machine Design, Manufacturing Processes and Vibrations. Simultaneously, the process of building the structure was conducted, concerning the search for resources, adapting the theoretical design when needed, and also the documentation and training of the future users. Finally, the project showed satisfactory characteristics considering the primary objectives, and a high reproducibility. It has the potential to present positive social effects and reduce the environmental impact of glass waste. The process by which it was conducted was very simple and efficient, especially regarding the use of basic concepts and simple mathematical relations instead of complex analyses, favoring its application in other low-resource projects aiming mainly for a high safety factor.